2022
DOI: 10.3390/ijms23063136
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Corneal Myofibroblasts Promote Corneal Epithelial Cell Migration

Abstract: Corneal epithelial wound healing is a multifaceted process that encompasses cell proliferation, migration, and communication from the corneal stroma. Upon corneal injury, bidirectional crosstalk between the epithelium and stroma via extracellular vesicles (EVs) has been reported. However, the mechanisms by which the EVs from human corneal keratocytes (HCKs), fibroblasts (HCFs), and/or myofibroblasts (HCMs) exert their effects on the corneal epithelium remain unclear. In this study, HCK-, HCF-, and HCM-EVs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…CD9 was also detected, although it showed a differential expression, only being identified in exosomes of healthy cells at the level of detection used in this work. On the other hand, CD63 was not detected, which is in line with previous studies of the proteomic profile of the corneal tissues where this protein was also not detected [ 20 ], although in another recent study CD63 was detected in isolated extracellular vesicles of keratocytes, although its levels increased markedly when transformation into fibroblasts occurred [ 52 ], which supports the notion, as shown by our controls, that the cells maintain a stable phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…CD9 was also detected, although it showed a differential expression, only being identified in exosomes of healthy cells at the level of detection used in this work. On the other hand, CD63 was not detected, which is in line with previous studies of the proteomic profile of the corneal tissues where this protein was also not detected [ 20 ], although in another recent study CD63 was detected in isolated extracellular vesicles of keratocytes, although its levels increased markedly when transformation into fibroblasts occurred [ 52 ], which supports the notion, as shown by our controls, that the cells maintain a stable phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…In a similar study, it was shown corneal epithelial-EVs have the capacity to influence the transdifferentiation of human conjunctival and corneal epithelial cells [ 124 ], or EVs pre-treated with thrombospondin-1 promoted tissue remodeling and repair [ 125 ]. More recently, our study examined the paracrine crosstalk from the corneal stromal (keratocytes, fibroblasts, and myofibroblasts) EVs and how they influence corneal epithelial wound healing [ 23 ]. The study provides evidence that corneal myofibroblast EVs compared to keratocyte- or fibroblasts-EVs contain distinct cargo proteins that promote corneal epithelial cell proliferation, migration, and motility.…”
Section: What Roles Do Extracellular Vesicles Play In Corneal Fibrosi...mentioning
confidence: 99%
“…The earliest evidence of EV involvement in corneal wound healing began in 1987 from in vivo rabbit keratectomy research [ 122 ]. The functional role of cell-to-cell communication has shown to be mediated by EVs during corneal wound healing, where the corneal epithelium interacts with stromal keratocytes, fibroblasts, and vascular endothelial cells [ 11 , 12 , 20 , 21 ], while corneal stromal EVs interact with corneal epithelial cells [ 23 ]. In another study, limbal stromal cell derived exosomes have been reported to promote proliferation and regeneration of limbal epithelial cells [ 13 ].…”
Section: Can We Utilize Extracellular Vesicles In Treatments Regiment...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ECM contributes to cell migration: The ECM regulates cell migration speed and direction, serving as a scaffold for cell migration [ 46 ]. For example, fibronectin promotes fibroblasts and corneal epithelial cell migration, while laminin promotes the migration of many tumor cells [ 47 ]. Moreover, chemotaxis and chemotactic migration rely on the ECM, implying embryonic development and wound healing.…”
Section: Extracellular Matrix (Ecm)mentioning
confidence: 99%